"Sustainability state" in the making? Institutionalization of sustainability in German federal policy making. - Heinrichs, Harald; Laws, Norman (MDPI, 2014)
More than two decades after the Rio-conference on environment and development in 1992, sustainable development remains a big challenge. Politics and administration, especially in democratic societies, have a specific responsibility in coordinating sustainable development. In order to fulfill this role, the regulative idea of sustainability needs to be integrated into decision-making in politics and administration at all levels, from local to global. Taking this into account, we have analyzed the institutionalization of sustainability as a crosscutting and long-term challenge at the federal level in Germany. Based on a theoretical-conceptual framework deriving from democracy, bureaucracy and political steering/governance theory, we have employed qualitative methods to understand, in depth, how sustainability is integrated into political-administrative practice. In the present paper, we present key results and show that sustainability is not a routine practice at the federal level in Germany. We will conclude by giving an outlook on the structural and procedural options and argue for the need to develop a "sustainability state".
Keywords: Umweltpolitik; Leitbild; Entscheidungsfindung; Bund; Land; Gemeinde; Nachhaltigkeit; Institutionalisierung; Nachhaltige Entwicklung; Governance